The Mediating Effect of the Intention to Quit as the Impact of Locus of Control on Dysfunctional Audit Behavior - Iman Supriadi (Ilomata International Journal of Tax and Accounting, 2023)
Auditing is an essential process in maintaining accountability and transparency within an organization. However, some dysfunctional audit behaviors can threaten audit integrity and cause significant losses to the company. This study aims to prove whether or not the intention to quit can mediate the indirect effect between locus of control on auditor acceptance of dysfunctional audit behavior, especially in all Public Accounting Firms in East Java Region. This is a quantitative causality research, and the data source in this study are generated from the primary data. The data are obtained from the respondents' answers to questionnaires given to all auditors who work at public accounting firms in East Java region. The 11 items-questionnaire was distributed via Google form. The results indicated that locus of control has a positive effect on auditors’ acceptance of dysfunctional audit behavior, intention to quit has a positive effect on auditors’ acceptance of dysfunctional audit behaviors, and locus of control has a positive effect on the intention to quit. Finally, the intention to quit is able to mediate the indirect effect of locus of control on auditors’ acceptance of dysfunctional audit behaviors.